U.S. Catholic Surveys: A Historiography of the Beginnings and Endings of American Catholicism - Mize, Sandra Yocum (US catholic historian, 2023)
Michel de Certeau’s The Writing of History guides a consideration of the historiography of U.S. Catholic surveys with a particular focus on how each survey begins and concludes. In examining the intricacies of historiography (the writing of history), Certeau observes how a historiographer (the writer of history) always seeks to “rejoin a present” with his or her history’s terminus, even one in the distant past. The historiographer also must choose “a zero-point” that begins, and thus orients, his or her account of the past. An examination of the beginnings and endings of fifteen U.S. Catholic surveys, which include two revised editions and span a period from 1879 to 2020, brings to light not only the many “presents” which U.S. Catholic historiographers sought to rejoin to the past but also the surprising number of “zero-points” that marked the beginning of U.S. Catholicism or, as it is more frequently identified, American Catholicism.